2006
DOI: 10.1029/2006gl026161
|View full text |Cite
|
Sign up to set email alerts
|

Control of equatorial ionospheric morphology by atmospheric tides

Abstract: [1] A newly discovered 1000-km scale longitudinal variation in ionospheric densities is an unexpected and heretofore unexplained phenomenon. Here we show that ionospheric densities vary with the strength of nonmigrating, diurnal atmospheric tides that are, in turn, driven mainly by weather in the tropics. A strong connection between tropospheric and ionospheric conditions is unexpected, as these upward propagating tides are damped far below the peak in ionospheric density. The observations can be explained by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

50
682
3
3

Year Published

2011
2011
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 597 publications
(761 citation statements)
references
References 26 publications
(30 reference statements)
50
682
3
3
Order By: Relevance
“…7, a large-scale longitudinal structure, which is similarly reported by many scientists (e.g. Sagawa et al, 2005;Immel et al, 2006;Lin et al, 2007;Kakinami et al, 2011), is clearly seen around the magnetic equator in the F3/C model. According to Kakinami et al (2011), the 4-peak structure of N e at 660 km observed with the DEMETER satellite is the most pronounced in September while a 3-peak structure appears in March and December.…”
Section: Resultssupporting
confidence: 59%
“…7, a large-scale longitudinal structure, which is similarly reported by many scientists (e.g. Sagawa et al, 2005;Immel et al, 2006;Lin et al, 2007;Kakinami et al, 2011), is clearly seen around the magnetic equator in the F3/C model. According to Kakinami et al (2011), the 4-peak structure of N e at 660 km observed with the DEMETER satellite is the most pronounced in September while a 3-peak structure appears in March and December.…”
Section: Resultssupporting
confidence: 59%
“…A good example is the recently discovered four maxima structure in the longitudinal variation of F-peak electron density and of ionospheric electron content that was first observed with IMAGE/EUV observations (Immel et al 2006), and then confirmed with data from CHAMP (Lühr et al 2007) and TOPEX (Scherliess et al 2008), and that is thought to be caused by nonmigrating, diurnal atmospheric tides that are driven by tropospheric weather in the tropics. While theoretical models still struggle to include this phenomenon in their modeling framework, inspection of the longitudinal variation of the F-peak density value NmF2 in IRI revealed that IRI already reproduces this phenomenon (McNamara et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A prominent four-peak longitudinal structure of the equatorial ionization anomaly (EIA) has been discovered by global satellite observations [e.g., Sagawa et al, 2005;England et al, 2006a;Immel et al, 2006;Lin et al, 2007]. In addition, according to modeling works, the longitudinal dependence of tropospheric convection has been shown to be an important source for the excitation of solar nonmigrating (non-Sun-synchronous) tides that propagate upward to the thermosphere, including the diurnal eastward-propagating tide with zonal wave number 3 (DE3), which has four peaks in the local-time fixed frame [e.g., Forbes, 2002, 2003;Miyoshi, 2006].…”
Section: Introductionmentioning
confidence: 99%